Pengaruh Kebijakan Fiskal Pemerintah Terhadap Pertumbuhan Ekonomi: Sebuah Analisis Literatur - Al-Amin (Adiba Aisha Amira, 2024)
Fiscal policy is one of the important instruments used by the government in regulating a country's economic growth. This study aims to systematically analyse the existing literature on the effect of fiscal policy on economic growth. Through an in-depth literature review, this study examines various theoretical and empirical approaches to fiscal policy, including aspects of government spending and tax revenue, and their impact on economic growth. The analysis includes various case studies from countries with different economic conditions to assess the effectiveness of fiscal policy in diverse contexts. The results indicate that fiscal policy has a significant role in influencing economic growth, but its effectiveness is highly dependent on country-specific conditions as well as the design and implementation of the policy. This research suggests that policymakers design fiscal strategies that not only focus on the short-term, but also support long-term economic growth by considering the balance between government spending and tax revenue. Through this literature analysis, it is expected to provide a more comprehensive view of the dynamics between fiscal policy and economic growth and pave the way for further research in this area.